The role of digitization and management in the electronic valuation of human resources management - خيرة بن يمينة; نشأت ناشد; زادي احمد (Journal of Distance Learning and Open Learning, 2019)
There is no doubt that the technological development in the world of electronic digitization of human resources in various organizations has become inevitable and necessary because of the nature of the rapid and successive changes in the field of human resources management in contemporary time. This is to enable strategic decision makers to know the comprehensive and accurate changes within the organization Both internal and external, giving the organization credibility and transparency in making informed decisions based on an efficient and accurate information system.